Monte Carlo simulation: transforming decision making in light of the Columbia Space Shuttle disaster - Clemen, Robert (Henry Stewart Talks, 2019)
This case study demonstrates how Monte Carlo simulation helped identify high-risk heat tiles on the Columbia Space Shuttle to improve safety in the wake of the Columbia Space Shuttle disaster of 2003.